DEPENDENCE OF COMPANY’S SHARE VALUE ON THE MARKET RATHER THAN ITS ASSEST VALUE - Gupta, Sonia (2009)
This research study mainly focuses on the various factors which affects share price .During my research an attempt has been made in finding the reasons that mainly lead to the fluctuation in share prices irrespective of the fact that asset value of the company remains the same. The detailed impact of the factors which affects the share prices of a company have been discussed and these factors are further divided into sub factors of macroeconomic, information, new financing, demand and supply and index construction. Further while discussing the analysis, the focus is mainly on three factors namely macroeconomic factors, industry analysis, and change in government policies. In macro economic factors, five different sectors are taken. In each sector a company has been discussed so as to show the effect of global crisis (macroeconomic factor) on each sector. The whole idea behind taking these sectors is to show that macroeconomic factors have an impact on all the sectors. Subsequently industry analysis has been discussed through an example of monsoons along with its impact on particular industries. Lastly, the effect of change in government policy has been discussed through an example of Ban on Participatory Notes in India with respect to its effect on the share market. At last, I have concluded that all the factors which are discussed above affects the stock market to great extent.